WHAT MAKES UNIVERSITY STUDENTS SWEAR - Svitlana Babushko; Liudmyla Solovei (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The problem of swearing by youth in public is becoming acute nowadays. A growing tendency can be traced in Ukraine that young women are on equal terms with men in this respect. The authors of the article explored the reasons of using non-standard language by Ukrainian students under modern conditions and specified what should be done to improve their speech culture and eliminate their swearing. The primary aim of the research is to find out the motives why Ukrainian university students swear in their everyday life. To achieve the goal a special questionnaire was designed. All in all, 118 respondents of 2 age groups participated in the survey. Differences and similarities in using swear words by junior and senior students were investigated according to 3 criteria: motives, types of emotions, recommendations of eliminating or at least minimising this phenomenon. As it is shown by results of the research, the most typical motive of using non-standard language for males and females is the opportunity to express both negative and positive emotions. Neither juniors nor seniors considered it to be extraordinary. Yet, they agreed that various educational activities should be arranged to eliminate the usage of swear words and uplevel the speech culture of university students.